Power Balance AODV Algorithm of WSN in Agriculture Monitoring - Dengyuan Xu; Shixun Wu; Benniu Zhang; Xiaoqin Qin (Universitas Ahmad Dahlan, 2013)
WSN (wireless sensor networks) is a kind of energy-constrained network, which has been widely used in precision agriculture environment monitoring. However, power balance is not taken into account in traditional routing algorithms. In this paper, a novel Power Balance Ad hoc On-Demand Distance Vector (PB-AODV) routing algorithm is proposed on cross-layer design to solve the problem of power balance. The main idea of our proposed algorithm is that, routing path is established by the received signal strength indication (RSSI) value in the route discovery process of PB-AODV. The optimal transmitting power which can be computed by RSSI value, power threshold and node’s surplus energy is encapsulated into route reply packet (RRP). Thus, the sender node can adaptively adjust its transmission power to save energy with the RRP. Simulation results show that the proposed algorithm is effective for load balancing, and increases the WSN’s lifetime about 14.3%.